EPT no ensino médio: institutos federais e escola unitária - Feijó, Jerciano Pinheiro (2022)
The dominant education model is directly associated with the economic, social, historical and cultural reality of the given society. It is no different, especially in the economic field, the country was influenced by the transformations that took place on a global scale. These changes have an impact on educational processes. In this way, based on a work of bibliographic review, through readings, reflections and textual production referenced in MARX (1985), GRAMSCI (1991), NOSELLA (1997), FRIGOTTO (1993) among others, Laws and Decrees on EPT, and empirical from the analysis of the organizational model of the IF'S having as reference the Campus Caucaia of the IFCE and of the state schools of the State of Ceará, this study intends to analyze the organizational parameters of the Federal Institutes in the light of the unitary school of Antônio Gramsci, in a way to debate as an educational principle the general, scientific culture of the cultural heritage of humanity, as well as the objective and critical understanding of reality, associated with physical development, that is, an omnilateral formation. Pointing, as a hypothesis, the way to build a single school system, having as reference the Federal Institutes of Education, Science and Technology. To achieve this objective, we will follow the historical path of Vocational Education in the country, developing an analysis based on MarxistGramscian thought, seeking to identify the influences that are manifested in the formative processes in EPT. Thus, we can see that assuming Gramscian thought, it is from within capitalist society that the new will emerge, the class struggle only ends when they no longer exist, therefore, there is the possibility of building a new hegemony and leading the State to carry out a omnilateral school, for that, it is necessary to change the hegemonic conjuncture of the country. Gramsci pointed out the role of the party as a revolutionary vanguard, today, we conclude that it is possible to say that due to the scope of the school that reaches all corners of the country as well as the absolute majority of young people, since we are moving towards universalization of basic education, a federalized school network and developed along the structural lines of the IF's, and that maintains the omnilateral educational principle, could be this bastion that will elevate us to a new social level.